The Influence of School Environment and Teacher Communication on Economics Teacher Competence in Jambi Province - Wiwik Pudjaningsih; Nurpeni Nurpeni; Herman Budiyono; Zuhri Saputra Hutabarat; Baseran Nor; Ade Taufan; Hendra Rustantono (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to analyze the effect of the school environment and teacher communication on the competence of economics teachers. The study used quantitative research design approach by using a survey model. The participants in this study were 142 teachers from public and private vocational high schools in Jambi Province and and using the Slovin formula to represent the entire population of 264 teachers. Furthermore, the data were analyzed using exploratory factor analysis, confirmation of theoretical factor analysis, and structural equation modeling. The findings in this study the school environment, teacher communication, and teacher competence can understand students by utilizing the principles of student cognitive development so that teachers can understand student personality development and reflect on it in the learning process, helping teachers to have the opportunity to apply material learning theories to daily life activities, and broaden the ideas and thoughts that the teacher has to students so that students understand the learning material provided.  The conclusion in this study is that learning in the school environment, teacher communication, and good teacher competence can increase understanding, interest, make student learning more enjoyable, and direct student learning activities to be more active.